Avoiding boredom: Caudate and insula activity reflects boredom-elicited purchase bias. (July 2017) - Dal Mas, Dennis E.; Wittmann, Bianca C.
Abstract: People show a strong tendency to avoid boring situations, but the neural systems mediating this behavioural bias are yet unknown. We used functional magnetic resonance imaging (fMRI) to investigate how the anticipation of a boring task influences decisions to purchase entertainment. Participants accepted higher prices to avoid boredom compared to control tasks, and individual differences in boredom experience predicted the increase in price. This behavioural bias was associated with higher activity in the caudate nucleus during music purchases driven by boredom avoidance. Insula activation was increased during performance of the boring task and subsequently associated with individual differences in boredom-related decision making. These results identify a mechanism that drives decisions to avoid boring situations and potentially underlies consumer decisions.